Seeking Help in the "Perfect Storm": Why Residents and Faculty Access an On-Site Wellness Program. (May 2021) - Ey, Sydney; Ladd, Benjamin; Soller, Marie; Moffit, Mary
Background: In the face of significant distress among physicians, access to counseling is critical. Objective: An on-site wellness program for physicians-in-training and faculty was assessed by examining (a) were participants representative of those eligible for services and (b) demographic and trainee vs. faculty differences in burnout, distress, suicide risk, and presenting concerns of participants who utilized services. Methods: From 2013–2018, 73% (N = 468; 316 residents/fellows, 152 faculty) of individuals seeking services also consented to research. At intake, participants completed a distress measure (ACORN) and two items from the Maslach Burnout Inventory (MBI), and clinicians categorized presenting concerns and suicide risk. Using Chi-square analyses, participants' characteristics were compared to physicians eligible for treatment. The association between demographics, faculty vs. trainee status, specialty, and distress, burnout, suicide risk, and presenting concerns was evaluated with ANOVAs and logistic regressions. Results: Women, trainees, and primary care physicians were more likely to access services. On the ACORN, 63% were in the clinical range (M =1.7, SD =0.6). On the MBI, 36% scored in the clinical range. Clinicians rated 9% of participants with suicide risk. Neither gender, racial/ethnic minority status, nor specialty were associated with distress, burnout or suicide risk. Trainees reported greater distress than faculty ( F (1, 447) = 8.42, P  =   .004, η p 2  = .018). Participants reported multiple presenting concerns (M = 3.0, SD = 1.18) with faculty more commonly endorsing work-related issues. Trainees more commonly reported new or worsening psychological symptoms, performance and family concerns. Conclusions: Two physician groups which often report higher levels of burnout and distress when surveyed, women physicians and residents/fellows, were the most likely to get professional help in an on-site wellness program. Physician wellness programs need to be prepared to address work and personal stressors and different levels of distress and risk.